Technical Efficiency Performance of Terubok Fisheries in Sarawak - Muhammad Ashraf, Bin Roszopor (Universiti Malaysia Sarawak (UNIMAS), 2019)
Terubok fish is an estuarine fish that is significant among local fishermen and in recent years, Sarawak has experienced a declining trend in the Terubok production. In order to increase the production of the Terubok fish supply, the fishermen have to focus more on the production efficiency of the fisheries. Hence, this study was carried out to analyse the efficiency performance of Terubok fisheries in Sarawak. A sample of 200 active Terubok fishermen was selected through stratified random sampling and field survey were conducted in core areas of Terubok fish. Data Envelopment Analysis (DEA) and Tobit analysis were employed to determine the technical efficiency level and factors influencing technical efficiency among Terubok fishermen. The results showed that the level of technical efficiency, pure technical efficiency and scale efficiency was estimated at 0.304, 0.406 and 0.805 respectively. The regression results showed that there was a nexus between efficiency and hours in a day, days spent fishing in a month, engine horsepower and fishermen’s association; while age, education, distance and length of vessels showed a negative relation towards efficiency. Additionally, age and hours of fishing were found to be significant with technical efficiency. These findings suggest that there is much room for improvement in efficiency among a large segment of Terubok fishermen. Thus, with appropriate training and the use of more advanced technologies of the fishermen, the level of Terubok fishermen’s efficiency can be raised.